Identification of non-halal recycled cooking oils using differential scanning calorimetry (DSC) combined with principal component analysis (PCA) - M.S, Mualim; Tukiran, Nur Azira; Abdullah Sani, Muhamad Shirwan; Fadzillah, Nurrulhidayah (Politeknik Nilai Negeri Sembilan (PNS), 2018)
Recycled cooking oil was used to save costs. The practice is worrying as recycled cooking oil taken from non-halal food premises should not be used by halal food premises. Therefore, an appropriate method should be developed in order to monitor the halal status of these cooking oils. Means of identifying recycled cooking oils (palm oil) that have been used for frying pork were investigated in this study. Pork and chicken were fried in palm oil heated up to 180oC. The cooking oil that has been used for frying pork (P) and chicken (C) containing 0.5-50% v/v of mixture of P and C were analyzed for thermal profile using differential scanning calorimetry (DSC) combined with Principal Component Analysis (PCA). The method used was able to identify cooking oils that have been used for frying pork in different percentage of mixture. The simple approach employing DSC and PCA reported in this paper may provide a useful tool for monitoring the halal status of recycled cooking oils